The effect of defect emissions on enhancement photocatalytic performance of ZnSe QDs and ZnSe/rGO nanocomposites - Yousefi, Ramin; Azimi, Hassan Rayat; Mahmoudian, Mohammad Reza; Basirun, Wan Jefrey (Elsevier, 2018)
A systematic study about the origin of defects emission of ZnSe structure was conducted by photoluminescence (PL) spectrometer at room temperature. It was observed that different intermediate energy levels in band-gap space of ZnSe structure were generated by different defects such as Se-, Zn-vacancies, Se-, Zn-interstitials, and surface states. Effects of these defects on the photocatalytic performance of ZnSe quantum dots (QDs) and ZnSe/graphene nanocomposites were investigated. The pristine ZnSe QDs and ZnSe/graphene nanocomposites were synthesized by a co-precipitation method. The PL spectra of the samples showed four emissions from four regions of the visible spectrum such as violet, green, orange, and red emissions. The violet emission was associated with the near-band-edge (NBE) of the ZnSe nanostructures, while, the other emissions were related to different defects of ZnSe structures. Annealing the samples in the H2 atmosphere caused to increase orange emission intensity and indicated that origin of orange emission was a donor-acceptor pair (DAPs) related to singly positively charged Se-vacancies (VSe) to singly negatively charged zinc vacancy (VZn −). Photocatalytic study of the samples to remove the methylene blue (MB) dye showed that the photocatalytic performance of the samples improved by graphene as an additive and increasing the orange emission intensity.